Kemampuan Menyelesaikan Soal Cerita Dalam Materi Trigonometri Berdasarkan Tahapan Polya - Rochyani, Wenti - (UNIVERSITAS TANJUNGPURA, 2025)
This study aims to describe the ability of grade X students at SMK Negeri 2 Pontianak in solving trigonometry story problems based on Polya's stages, viewed from the level of mathematical ability. This study uses a qualitative descriptive approach. The data collection technique used a test in the form of an essay for students in class X TKR B at SMK Negeri 2 Pontianak and interviews conducted with 6 students, with 2 students each from the high, medium and low mathematics ability levels. The results of the study indicate that students with high and moderate mathematical ability are able to perform the problem-understanding stage, but not all students with low mathematical ability are able to perform the problem-understanding stage. Not all students with moderate mathematical ability are able to perform the planning stage, and students with low mathematical ability are not yet able to perform the planning stage. Not all students with high and moderate mathematical ability are able to carry out the plan implementation stage accurately, and students with low mathematical ability are not yet able to carry out the plan implementation stage. Not all students with high mathematical ability are able to carry out the review stage, and students with moderate and low mathematical ability are not yet able to carry out the review stage.